(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objectives: To estimate the frequency and relation of polycystic ovarian syndrome (PCOS) with hirsutism in normal and hirsute females. Study Design: Cross-sectional analytical study. Place and Duration: Department of Dermatology, Radiology and Immunoassay Laboratory at NHRC, Sheikh Zayed Medical Complex, Lahore from Dec 2008 – Dec 2009. Patients and Methods: Clinically confirmed 50 hirsutes and 50 normal females aged between 14-20 years were included in the study while those with virilism, post menopausal, menopause cushing syndrome were excluded. Informed consent was obtained from eligible participants and demographic information was recorded in a study proforma. Ultrasound was done for polycystic ovaries (PCO) and adrenal hyperplasia. PCOS was further confirmed in accordance with revised Rotterdam definitions 2003 and its criteria. A modified Ferriman-Gallwey (FG) score was used to determine the severity of hirsutism. Five milliliters of fasting blood was drawn, serum separated and stored at -20ºC, for analysis of luteinizong hormone and follicular stimulating hormone ratio (LH: FSH), free testosterone, dihydrotestosterone (DHT), cortisol and alanine transferase (ALT). Results: A total 100 young females were studied. Most of the hirsute females (80%) had moderate to severe hirsutism. PCO was confirmed in 68% hirsute and 32% normal age matched group. Oligomenorrhea was present in 44% hirsute female and 4% normals. No direct association was seen among obesity, hirsutism and PCO. Disturbance of LH:FSH ratio was seen in all hirsute females with PCO while LH:FSH ratio was found normal in all PCO negative hirsutes and control females. Mean levels of free testosterone, DHT, cortisol and ALT were normal in both groups. Conclusion: About 68% hirsute and 32% normal females had PCO. The chances of having hirsutism in adolescents suffering from PCO alongwith oligomenorrhea is higher than that of in females with PCO alone.